EARTH HOUR'S ADVERTISEMENTS AND LOGO AS ENVIRONMENTAL PROTECTION PROGRAM BY WORLD WIDE FUND - ADITAMA, YUDHA SATRIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: advertisement, logo, semiotics, world wide fund, earth hour. Logo is an identity or special symbol that represents a company or organization. In this study, semiotics approach from Ferdinand de Saussure is used to analyze the logo and its advertisements. Advertisement is a medium to deliver messages to society with the goal to influence the people to join or follow certain programs. Non-verbal and visual signs are used in advertisement and logo. This study is conducted to explore signs, meanings, and messages constructed in logo and its advertisements of World Wide Fund.Among a lot of advertisements and logos that have been published by WorldWide Fund, the writer analyzes four different advertisements and one logo. In this study, the writer analyzes two advertisements of Earth Hour “For a Living Planet” and two advertisements “You Can’t Afford to be Slow in an Emergency” and logo of Earth Hour program. After  analyzing  the  signs,  it  can  be  concluded  that  every single signifier on each  advertisement have different  meanings and messages. The messages from the logo and its advertisements are related to the efforts in preserving and protecting the nature, including the animal populations. It can be also figured out that the advertisements are designed to persuade the society to join Earth Hour as the environmental protection program.The writer suggests English Department students to learn more about semioticsespecially for analysing advertisement. The writer also suggests the next researchers to conduct a semiotics study in advertisement videos or use other semiotics theories.